Barras estruturadas mistas de manga e cajá adicionadas de extrato bioativo de caju: aspectos tecnológicos e capacidade antioxidante - Santiago, Keliane Lima (2021)
This work has the objective of developing and characterize mixed structured bars from cajá and mango with the addition of a cashew co-product extract as well to assess your sensory acceptance. First, four formulations were developed that varied in the content of mango pulp (M) and cajá (C), as well as sugar (A), namely M50/C50/A5, M50/C50/A0, M75/C25/A0 e M75/C25/A5 that were prepared without the addition of the extract and subjected to affective and descriptive sensory tests such as CATA and RATA (Sensory Evaluation I). From these results, news formulations were developed with the adiction of bioactiv extract (E) E25/A0, E25/A5, E15/A0, E15/A5. A control formulation (E0/A0), no added extract and sugar was also elaborated. This samples were subject to an ordering-preference test. The structured bars of mango and cajá and the extract were characterized according to the physical-chemical parameters (pH and soluble solids), physical (water activity, humidity and color), antioxidant compounds (vitamin C, total phenolics) and total antioxidant activity (FRAP and ABTS method). The extract and the bars presented a high humidity and water activity, low acidity, and soluble solids content. Considerable amounts of ascorbic acid were found in the extract (25,78 mg AA/100 g), which showed higher values than fruits like mango and soursop. Moreover, the extract showed high values of total phenolic compounds (283,52 mg GAE/100 g) and significant values were also found for the antioxidant capacity that was determined by the FRAP (55,3 µM Fe2SO4/g) and ABTS (21,79 µM Trolox/g) methodologies, even though it is a by-product of processing. In turn, the structured mango and cajá bars added to the extract showed high values of ascorbic acid (ranging from 32,13 a 49,97 mg AA/100 g) and total phenolic compounds (ranging from 59,04 a 88,05 mg GAE/100 g). Finaly, afer the applying the preference ordering test, the tasters showed preference for the formulation composed of 25% of the extract and 5% of sugar, showing the feasibility of adding the developed extract to the mixed structured bars, as an alternative to enrich this product, as well as the use of this industrial co-product, implying an increase in the added value of these products, to allowing the opening to new possibilities for large-scale fruit industrialization, as well as boosting the opening of new consumer markets.